16Digital Humanities. - Mandal, Anthony (Year's Work in Critical & Cultural Theory, 2018)
This chapter examines material published in the field of digital humanities in 2017. Owing to controversial developments in the political sphere, public awareness of the role of big data in our lives has grown. Anxieties about 'microtargeting' and 'dataveillance' inflect our increasingly troubled relationship with computational culture, particularly as the commercialization of the Internet and its fragmentation into proprietary platforms mean that algorithmic and machine-learning processes are hidden away from scrutiny in 'black box' systems. Books by Nick Srnicek and Richard J. Lane discuss the turn towards big data and platforms, detailing the ways in which humanities scholars might engage with such transformations. A second strand of digital culture looks at the relationship between humanity and machines, with the material turn encouraging more sustained examination of 'digital bodies'. This is the name of the collection edited by Susan Broadhurst and Sara Price, who bring together essays from a range of artists, performers, fashion designers, and sociologists. Looking at the augmentation of humanity by the digital, Andrew Pilsch aims to rehabilitate the transhumanist movement in scholarly circles by relocating it within a longer tradition of utopian evolutionary futurism that can be traced back to the early twentieth century. By contrast, N. Katherine Hayles turns to cognitive processes, arguing that recent discoveries in neuroscience regarding nonconscious cognition can realign our understanding of the relationship between humanity and machine. The final part of this chapter looks at recent monographs by David Berry and Anders Fagerjord and by James Smithies that propose new inflections of the digital humanities in response to the challenges outlined in the foregoing discussion.